Freshwater decapod crustaceans from the state of Minas Gerais, Brazil: species composition and distribution - Jacobucci, Giuliano Buzá; Bueno, Alessandra A. De P.; Almeida, Ariádine Cristine De; Alves, Douglas Fernandes Rodrigues; Barros-Alves, Samara De Paiva; Magalhães, Célio; Souza-Carvalho, Edvanda A.; Mossolin, Emerson C.; Carvalho, Fabrício Lopes; Mantelatto, Fernando L. (Zootaxa, 2023)
Brazil contains about 5% (~120 spp.) of the total known species of freshwater decapods. Information on the occurrence of freshwater decapod species in the state of Minas Gerais is dispersed and much of this remains unpublished. We hereby propose to present the first inventory of freshwater decapods from the state, based on data compiled from publications and scientific collections and obtained from fieldwork in the state. Eleven species of freshwater decapods were recorded in Minas Gerais, including three species of crabs (Trichodactylidae), seven of shrimps (Palaemonidae) and one species of freshwater squat lobster (Aeglidae), classified into three infraorders, three families, and four genera. The genus Macrobrachium C.S. Bate, 1868 comprised most of the decapod records. The reduced number of species in relation to coastal states is related, at least in part, to the absence of amphidromic species. Environmental degradation and the construction of dams in several watersheds may be possible causes of this absence. The records obtained from surveys carried out in national parks situated in Minas Gerais and its surroundings indicate the importance of these areas for the conservation of decapod fauna in the state.